ANALISIS KEMAMPUAN MATEMATIS SISWA TERHADAP HASIL BELAJAR PADA MATERI TERMOKIMIA KELAS XI IPA 2 DI SMA NEGERI 15 SEMARANG - Abu To’at; Hidayah Hidayah; Fitria Fatichatul (Universitas Muhammadiyah Semarang, 2018)
Chemistry is part of the natural sciences, which includes the understanding of chemical concepts and calculations. These two concepts that should be owned by the students in understanding the chemistry so that students are easy to master the science of chemistry. The purpose of this research is to know the mathematical ability of students in class XI IPA 2 15 SMA N Semarang and to know the results of the study in terms of his mathematical ability of students on the material of Thermochemistry. The method of this research is descriptive.The data collected using the techniques of observation, measurement, andinterviews. The results of the analysis show that students have average math skills students of 62.74 measured at 6 indicators of the ability of mathematical material contained on Thermochemistry. The results of a study on the material of Thermochemistry students have an average of 51.95. Analysis of the students' answer sheets on the test results of the study showed that students already have a good math skills with percentage of 58.82%. The data also showed that students who have difficulty on the material of Thermochemistrybecause the students less understand the concepts of chemistry.Keywords : Mathematical Ability, The Results Of The Study, Thermochemistry